Effects of plant natural products on metabolic-associated fatty liver disease and the underlying mechanisms: a narrative review with a focus on the modulation of the gut microbiota - Cai, Tianqi; Song, Xinhua; Xu, Xiaoxue; Dong, Ling; Liang, Shufei; Xin, Meiling; Huang, Yuhong; Zhu, Linghui; Li, Tianxing; Wang, Xueke; Fang, Yini; Xu, Zhengbao; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Metabolic-associated fatty liver disease (MAFLD) is a chronic liver disease characterized by the excessive accumulation of fat in hepatocytes. However, due to the complex pathogenesis of MAFLD, there are no officially approved drugs for treatment. Therefore, there is an urgent need to find safe and effective anti-MAFLD drugs. Recently, the relationship between the gut microbiota and MAFLD has been widely recognized, and treating MAFLD by regulating the gut microbiota may be a new therapeutic strategy. Natural products, especially plant natural products, have attracted much attention in the treatment of MAFLD due to their multiple targets and pathways and few side effects. Moreover, the structure and function of the gut microbiota can be influenced by exposure to plant natural products. However, the effects of plant natural products on MAFLD through targeting of the gut microbiota and the underlying mechanisms are poorly understood. Based on the above information and to address the potential therapeutic role of plant natural products in MAFLD, we systematically summarize the effects and mechanisms of action of plant natural products in the prevention and treatment of MAFLD through targeting of the gut microbiota. This narrative review provides feasible ideas for further exploration of safer and more effective natural drugs for the prevention and treatment of MAFLD.